The CoViD-19 pandemic and mental health: Disentangling crucial channels - Bettina Siflinger; Michaela Paffenholz; Sebastian Seitz; Moritz Mendel; Hans-Martin von Gaudecker (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
Since the start of the CoViD-19 pandemic, a major source of concern has been its effect on mental health. Using pre-pandemic information and five customized questionnaires in the Dutch LISS panel, we investigate how mental health in the working population has evolved along with the most prominent risk factors associated with the pandemic. Overall, mental health decreased sharply with the onset of the first lockdown but recovered fairly quickly. In December 2020, levels of mental health are comparable to those in November 2019. We show that perceived risk of infection, labor market uncertainty, and emotional loneliness are all associated with worsening mental health. Both the initial drop and subsequent recovery are larger for parents of children below the age of 12. Among parents, the patterns are particularly pronounced for fathers if they shoulder the bulk of additional care. Mothers' mental health takes a particularly steep hit if they work from home and their partner is designated to take care during the additional hours.
Keywords: I10; I14; I18; I30; J22; 330; COVID-19; mental health; gender inequality; lockdown